2006
DOI: 10.1677/jme.1.02091
|View full text |Cite
|
Sign up to set email alerts
|

Impact of uncoupling protein-2 overexpression on proinsulin processing

Abstract: Hyperproinsulinemia is observed in type 2 diabetic patients. We hypothesized that the induction of uncoupling protein-2 (UCP2) would impair processing of proinsulin to mature insulin and potentially contribute to hyperproinsulinemia, based on the evidence that hormone processing is an ATP-dependent process and UCP2 up-regulation can suppress cellular ATP production. UCP2 was overexpressed (UCP2-OE) by twofold in INS-1 cells by means of plasmid transfection. Although UCP2-OE reduced glucose-stimulated insulin s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 60 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…There was no difference in accumulation of total insulin (data not shown); however, there was substantially more proinsulin in the media of CMPF-treated islets compared to controls, consistent with an altered proinsulin:insulin ratio observed in T2D patients (Kamoda et al, 2006) (Figure 5A). Impaired insulin processing has previously been associated with elevations in ER stress and/or reactive oxygen species (ROS) production (Wu and Kaufman, 2006;Kashemsant and Chan, 2006). CMPF treatment did not induce markers of ER stress including Chop, Bip, and XBP-1 as examined by microarray and qPCR (Figures S5A and S5B).…”
Section: Cmpf Directly Impairs B Cell Functionmentioning
confidence: 87%
“…There was no difference in accumulation of total insulin (data not shown); however, there was substantially more proinsulin in the media of CMPF-treated islets compared to controls, consistent with an altered proinsulin:insulin ratio observed in T2D patients (Kamoda et al, 2006) (Figure 5A). Impaired insulin processing has previously been associated with elevations in ER stress and/or reactive oxygen species (ROS) production (Wu and Kaufman, 2006;Kashemsant and Chan, 2006). CMPF treatment did not induce markers of ER stress including Chop, Bip, and XBP-1 as examined by microarray and qPCR (Figures S5A and S5B).…”
Section: Cmpf Directly Impairs B Cell Functionmentioning
confidence: 87%
“…The primary physiological function of mild uncoupling is to suppress oxygen radical production accompanied by restricting mitochondrial permeability transition pore opening and Ca 2 + accumulation (20). It also plays an important role in regulating the energy balance in many tissues such as pancreas, liver, and brain (10). It has been reported that UCP2 modulated intracellular energy metabolism and thus was involved in aging, diabetes, and neurodegeneration (5,34).…”
Section: Ucp2 Mediates Neuroprotective Effect Of H 2 Smentioning
confidence: 99%
“…Ucp2 is expressed in many tissues, including the pancreatic β cell [4], which relies heavily on glucose metabolism coupled to ATP production for efficient and appropriate insulin secretion. Not surprisingly, numerous gain-of-function [5], [6], [7], [8], [9], [10] and loss-of-function [11], [12], [13], [14], [15], [16] studies have been used to interrogate the function of UCP2 in the β cell and, for the most part, have established a negative relationship between UCP2 and glucose-stimulated insulin secretion (GSIS). For example, whole body ( Ucp2 -/- ) [11], [12] and β cell Ucp2 knockout ( Ucp2- βKO) mice [14] show augmented GSIS, whereas overexpression of Ucp2 in clonal β cell cultures and rat islets impairs GSIS [5], [9].…”
Section: Introductionmentioning
confidence: 99%